EVALUATION OF THE AGROINDUSTRIAL WASTES OF BANANA (Musa paradisiaca) AND SAWDUST OF ABARCO (Cariniana pyriformis) AS SUBSTRATES FOR THE CULTURE OF THE FUNGUS Pleurotus djamor - MOTATO R., Karina E.; MEJÍA G., Amanda I.; LEÓN P., Ángela (Vitae, 2009)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; @font-face font-family:Aldine401BT-RomanA; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"MS Mincho"; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 134676480 16 0 131073 0; @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; @font-face font-family:"\@Aldine401BT-RomanA"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:128; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 134676480 16 0 131072 0; @font-face font-family:TimesNewRomanPS-ItalicMT; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The development of the Pleurotus djamor fungi fruit body on banana (Musa Paradisíaca) and sawdust (Cariniana pyriformis) remainders is studied for seven different mixtures: sawdust (100%), leaves (100%), stem (100%), sawdust-leaves (50/50%), sawdust-stem(50/50%), sawdust-fruit (50/50%) and a final mixture of sawdust-leaves-stem-fruit(25/25/25/25%). The micelial growth is analyzed at different temperatures. A according to the maximum micelial diameter and the larger activities of the manganese peroxidasa and lacase enzymes that were obtained , the sawdust-leaves (50/50%) and leaves (100%) remainders were chosen as substrates for the culture of the Pleurotus djamor fungus. The leaves substrate (100%), is successful for development of P. djamor fruit body with an average biology efficiency of 24.1% ±-7.0 after two fungi growths. Bromatology characterization of the mushrooms and the substrate of leaves before and after of the fungi cultivation is done in order to determine the nutritional composition and possibilities of cultivation of this fungi on agroindustrial remainers , which are obtained in large amount in Colombia.